Understanding the key components of effective dementia education and training - Hill, James E (Br J Neurosci Nurs, 2022)
Inadequate and poor care can lead to reduced quality of life for people living with dementia and a higher overall cost to healthcare. Dementia education and training for health and social care staff has been set as a priority by the Department of Health. It is vital to identify what specific factors are important when undertaking dementia care training. This commentary article critically appraises and evaluates a systematic review based on identifying key factors in delivering effective dementia care training.